Flap Striae: Managing and Understanding Post-LASIK Complication - Khoirunnisa, Auliya; Nuramalia, Lady Sherly; Rasyda, Risnanda Putri; Dharmawidiarini, Dini (Universitas Airlangga, 2024)
Introduction: Flap striae is the most common postoperative complication, with a frequency ranging from 0.033% to 3.5%, according to studies involving over 1000 ocular cases. There is only one case in our hospital in 2023. In this case report, we will present a case of flap striae in a tertiary hospital because our findings are unusual and essential in symptomatic therapy and visual rehabilitation. Case Presentation: A 19-year-old female came with a chief complaint of impaired vision in her left eye for the past two weeks, followed by inability to focus, discomfort of the eye, a sensation of foreign body, and glare that occurred three days after she underwent bilateral myopia laser in situ keratomileusis (LASIK) surgery. A post-LASIK assessment found that both eyes had visual acuity 10/10, and the left eye's visual acuity dropped to 6/10. Slit lamp examination revealed flap striae were running from the superonasal to the inferolateral quadrant. The thickness disparities were measured using optical coherence tomography (OCT), ranging from 653 to 689 Î¼m. The OCT pictures revealed a gap on the temporal side as well. This patient was diagnosed with flap striae and a flap repositioning procedure was performed. Conclusions: A flap repositioning surgery was performed to increase visual acuity and eliminate striae.